การปรับปรุงขอบเขตการประมาณค่าสำหรับปัญหาการจับคู่ด้วยการแจกแจงปัวซง - ธนัชชา บุญญะ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Matching problem is the problem that needs to place n objects in the correct position. Let Wn be a random variable representing the number of objects that are in their correct position. It is well-know that for A ⊆ {0,1, …., n}, we can approximate P(Wn ∈ A) by P(P₁ ∈ A) where P₁ is a Poisson random variable with parameter 1. There are several researches that calculated bounds on the approximation. In this project, we improve the bound of the approximation by using Stein-Chen method. [equation]